Information technology for constructing the composite indices for data of different types used in medical and environmental studies - Antomonov, M.Yu. (Кибернетика и вычислительная техника, 2018)
The purpose of the paper is to develop a generalized information technology for constructing composite indices for different types of data used in medical and environmental studies.